Analysis of the Management and Use of Digital Illustrations as a Media to Represent Islamic Da'wah Messages on the Instagram Account @Akhlaqpedia - Romadlany, Zakiyah; Arifah, Dwi Fitrianti (Al-Qalam Institue, 2025)
The transformation of social media in the digital era has changed the way Islamic da'wah is delivered, including through communicative and aesthetic digital illustrations. Instagram has become a strategic platform for conveying da'wah messages visually in an engaging and contextual manner. This study aims to analyze the representation and management of Islamic da'wah messages through digital illustrations on the Instagram account @Akhlaqpedia using a descriptive qualitative method and Roland Barthes' semiotic analysis. The findings reveal that visual elements such as characters, colors, text, and symbols function not only as aesthetic tools but also as conveyors of meaning across three semiotic levels: denotation (realistic depictions), connotation (moral messages and spiritual calls), and myth (social constructions of ideal Muslim identity). In addition to visual interpretation, this study highlights the importance of digital content management in sustaining da'wah effectiveness ranging from content planning, visual consistency, to audience engagement strategies. The integration of creative design and structured content management enables @Akhlaqpedia to maintain relevance and trust among its followers, particularly the younger generation. This study contributes to the discourse on digital da'wah and provides insights for further research on media management, audience reception, and multimodal Islamic communication.